The Role of Employee Performance, Leadership, and Workload on Job Satisfaction (Literature Review Human Resource Management) - Reni Silviah (Greenation Research & Yayasan Global Resarch National, 2024)
Literature Review The Role of Employee Performance, Leadership and Workload on Job Satisfaction is a scientific article with the aim of analyzing whether employee performance, leadership and workload influence job satisfaction. A qualitative approach method using a literature review method to explore and analyze the relationship between leadership, workload and job satisfaction. The results of this article are: 1) Employee Performance plays a role in Job Satisfaction, 2) Leadership plays a role in Job Satisfaction; 3) Workload plays a role in Job Satisfaction. Apart from these 3 exogenous variables which influence the endogenous variable Job Satisfaction there are many other factors including motivation, environment, organizational culture, training.